Deep Fungal Infections Among General Hospital Inpatients in Southwestern China: A 5-Year Retrospective Study - Wen, Shu-Ran; Yang, Zheng-Hui; Dong, Tian-Xiang; Li, Yu-Ye; Cao, Ying-Kui; Kuang, Yi-Qun; Li, Hong-Bin (Frontiers in Public Health, 2022)
Background: Deep fungal infection is a type of life-threatening opportunistic infection, the incidence of which has been increasing in recent years. This infection can affect the prognosis of patients, prolong hospital stays and raise costs for patients and their families. Objective: We aimed to understand the current situation of deep fungal infections in the First Affiliated Hospital of Kunming Medical University, and to provide the basis for clinical diagnosis and treatment of deep fungal infections. Methods: A retrospective analysis was conducted on the hospitalized cases in the hospital from 2015 to 2019, including the epidemiological characteristics, treatment and prognosis of deep fungal infections. Results: A total of 274 cases (0.05%) with deep fungal infections were identified. The incidence of deep fungal infections in the hospital showed an increasing trend from 2015 to 2019. The most commonly infected site was the respiratory tract (93.07%). Candida albicans (60.53%) is the main pathogen. Antibiotics were the most common predisposing factor (97.45%). Infectious diseases (59.49%) were the most common basic diseases. Those with basic diseases such as renal insufficiency and neurological diseases had a worse prognosis than those without. Indwelling catheters, nervous system disease and tumors were risk factors of poor prognosis. Conclusions: We reported for the first time the epidemiological data of deep fungal infections in general hospitals in Southwest China from 2015 to 2019. Provide references for the diagnosis and treatment of deep fungal infections.